DETECTION ALGORITHMS AND THEIR IMPLICATIONS FOR PARTICIPATION: THE CASE OF MASHUPS - Brøvig-Hanssen, Ragnhild; Jones, Ellis (AoIR Selected Papers of Internet Research, 2020)
‘Mashup’ is a form of music that, in its use of samples from existing popular music recordings, has often been seen as an exemplar of the participatory cultural environment that many expected the internet to foster. It is a musical form that remains widely produced and consumed today. However, the contemporary internet is a complex environment for media distribution, with dominant platforms making use of a wide range of automatic and algorithmic regulatory tools in order to police, monitor, and remove unwelcome content – including that which is seen, rightly or wrongly, as copyright infringing. Drawing on recent empirical research on and with mashup producers – including 30 semi-structured interviews and an extensive survey (n=92) – this article explores the impact of platform regulation on mashup music today. It concludes that current regulation has significant stifling effects on this kind of remix creativity, including a substantial impact on where mashup producers distribute their music, on the aesthetics of their music, and – most pertinently – on their overall motivation to create. Having outlined these key findings, we argue that the ‘shutdown’ status of mashup producers raises profound questions concerning the balance between regulating online content in terms of protecting the artists’ rights, and cultivating participation and culturally valuable artistic expression. As such, this paper offers a timely contribution to scholarship on the complex relationship between popular music and new media in its critical exploration of internet’s detection algorithms and their implications for mashup music and cultural participation more generally.